12.1k views
4 votes
How do you simplify this?


(9k^(6)+8k^(4)-6k^(2))(4k^(2)-5)

1 Answer

2 votes

ANSWER


36k^(8) -13{k}^(6) -64k^(4) + 30 {k}^(2)

Step-by-step explanation

Recall the distributive property:


(a + b + c)(d + e) = a(d + e) + b(d + e) + c(d + e)

We apply this property multiple times to simplify


(9k^(6)+8k^(4)-6k^(2))(4k^(2)-5)

This implies that:


9k^(6)(4k^(2)-5)+8k^(4)(4k^(2)-5)-6k^(2)(4k^(2)-5)

We apply the distributive property again:

This time: a(b+c)=ac+ab


\implies \: 9k^(6) * 4k^(2)-5 * 9 {k}^(6) +8k^(4) * 4k^(2)-5 * 8 {k}^(4) -6k^(2) * 4k^(2) + 5 * 6 {k}^(2)


\implies \: 36k^(8) -45{k}^(6) +32k^(6) -40 {k}^(4) -24k^(4) + 30 {k}^(2)


\implies 36k^(8) -13{k}^(6) -64k^(4) + 30 {k}^(2)

NB:
k^(n)*{k}^(m)=k^(m+n)

User Yurko
by
5.2k points